(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The experiment was conducted to carry out the nitrogen fixing cyanobacterial (BGA) resources and their distribution pattern in rice fields of North-West region of Bangladesh during the period of 2011. Considering the vast importance of Blue-green algae (BGA) in agricultural land especially in rice fields, their twelve months long systematic was undertaken. A total of 10 genera with 37 species of filamentous-heterocystous blue-green algal forms were identified and recorded from this region. Out of 37 species, 9 species belonging to the genus Anabaena, 8 to Nostoc, 5 to Cylindrospermum, 4 to Calothrix, 3 to Rivularia, 3 to Gloeotrichia and 2 to Aulosira; while 1 species belonging to each genus of Anabaenopsis, Microcheate and Aphanizomenon. The distribution pattern of filamentous-heterocystous BGA in rice fields over the study area has also been observed in this study. With few exceptions, the filamentous-heterocystous BGA are more or less uniformly distributed all over the study areas. All of the BGA members have a tremendous ability to contribute on enhancing agricultural production by fixing atmospheric nitrogen and adding organic matter, vitamins, growth promoting substances etc to the soil and crops. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22075 J. Environ. Sci. & Natusral Resources, 6(1): 253-259 2013